Analisis Strategi Pengelolaan Media Sosial Dalam Menyebarkan Konten Berita Di Instagram Mata Milenial Indonesia TV Tahun 2023 - Galih Setyo Purwoko; Febriansyah Nataly (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2023)
The development of information technology has become one of the greatest innovations in human life. This is what creates a change in conventional media to become modern and completely digital. Among various social media platforms, Instagram is most likely to focus on visual content. The aim of this research is to analyze Mata Millennial Indonesia TV's social media management strategy to maintain its existence in broadcasting news content on Instagram using Instagram features. The research methodology used is a qualitative method by reducing data and presenting the data. The method used is purposive sampling, namely a non-random sampling method, where the author ensures the selection of informants through a method of determining special identities that are suitable for the research objectives, while data collection techniques are through in-depth interviews, observation and documentation to strengthen the theory. The results of this research are that Mata Millennial Indonesia TV uses Instagram in social media management as it focuses on selecting content that will provide added value, meet audience needs, and achieve the desired results by using straight news types that are made short, concise, straightforward. and what it is. So that it contains news value that is actual, interesting and gets feedback from its followers. Mata Millennial Indonesia TV builds strategies to guide decision making, resource allocation, and achieving desired results. By implementing four aspects of the circular model of social media management strategy in The Circular Model of Some, such as sharing, optimization, management and participation. Thus, online media companies that disseminate information all have a basis or plan to achieve their goals. By broadcasting viral events that become the subject of lively conversation with topical content in the form of videos accompanied by voiceovers and narrative text.